IMPROVING THE METHODOLOGY FOR DEVELOPING REFLECTIVE COMPETENCIES OF FUTURE FOREIGN LANGUAGE TEACHERS (International journal of artificial intelligence, 2025)
This paper explores ways to improve the methodology for developing reflective competencies among future foreign language teachers. Reflection is considered a key component of professional self-development, enabling teachers to critically evaluate their teaching practices, identify challenges, and seek effective solutions. The study emphasizes the importance of integrating reflective activities—such as self-assessment, peer feedback, and lesson analysis—into teacher education programs. It also highlights the role of digital tools and mentoring in fostering deeper levels of pedagogical reflection. The proposed methodological model aims to enhance the professional readiness, autonomy, and critical thinking of future educators, ultimately contributing to higher quality foreign language teaching and learning outcomes.